2008
DOI: 10.4315/0362-028x-71.6.1232
|View full text |Cite
|
Sign up to set email alerts
|

A National Survey of the Microbiological Quality of Retail Raw Meats in Australia

Abstract: A national survey of the microbiology of meat (ground beef and diced lamb) at the retail level in Australia was undertaken. For ground beef samples (n = 360), the mean aerobic plate count (APC) was 5.79 log CFU/g, and Escherichia coli was detected in 17.8% of samples; the mean population for these positive samples was 1.49 log CFU/g. Enterobacteriaceae were detected in 96.9% of samples (mean for positive samples, 3.01 log CFU/g), and coagulase-positive staphylococci were detected in 28.1% of samples (mean for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
23
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 13 publications
6
23
1
Order By: Relevance
“…Along with this Salmonella and Shigella species were detected from 47.62% of the total meat sample, so according to CFS, FSANZ AND CREC statute [7,8,13] almost half of the meat samples had unsatisfactory quality. This finding is comparable with different previse findings undertaken in abattoir, retaile raw meat and/ or meat productes [5,[14][15][16][17]; were detected Salmonella at different level from abattoir, meat and meat processing materials.…”
Section: Bacterial Countand Standardizationsupporting
confidence: 91%
See 3 more Smart Citations
“…Along with this Salmonella and Shigella species were detected from 47.62% of the total meat sample, so according to CFS, FSANZ AND CREC statute [7,8,13] almost half of the meat samples had unsatisfactory quality. This finding is comparable with different previse findings undertaken in abattoir, retaile raw meat and/ or meat productes [5,[14][15][16][17]; were detected Salmonella at different level from abattoir, meat and meat processing materials.…”
Section: Bacterial Countand Standardizationsupporting
confidence: 91%
“…Where the overall mean (3.867 ± 0.3 cfu/g) count is in accordance with a national survey of the microbiological quality of retail raw meats in Australia [14]. On the other hand according to CFS and FSANZ statute [7,8] 47.62% of the total sample were categorized in to each of borderline and unsatisfactory quality standard; while only the remain few samples had satisfactory quality.…”
Section: Bacterial Countand Standardizationsupporting
confidence: 63%
See 2 more Smart Citations
“…Two of the previous studies from the United States showed that the APC and number of coliforms in trimmed meat were approximately 2.7 log CFU/g (ranging from 1.9 to 3.6 log CFU/g) and 1.7 log CFU/g (0.8e2.5 log CFU/g), respectively (Kang et al, 2001a,b) Another study from Australia about E. coli concentration reported the mean population of E. coli in ground beef to be 1.5 log CFU/g (Phillips et al, 2008), which is apparently higher than the data in the present work.…”
Section: Microbiological Analysis and Prevalence Of Ehec In Frozen Mementioning
confidence: 99%